On computational complexity of a detailed routing problem in two dimensional FPGAs - Yu-Liang Wu; Shuji Tsukiyama; Malgorzata Marek-Sadowska (Great Lakes 4th Symposium on VLSI: Design Automation of High Performance VLSI Systems, 2002)
In this paper, we consider the problem of mapping a given global route to a detailed route for two dimensional homogeneous FPGAs. It has been shown that this problem is NP-complete on a popular Xilinx-4000-like routing architecture. Here, we further prove that this problem remains NP-complete for an arbitrary fixed switch box topology of the same connection flexibility, with or without doglegs allowed in detailed routes.< >